(S)-Goniothalamin induces DNA damage, apoptosis, and decrease in BIRC5 messenger RNA levels in NCI-H460 cells - Semprebon, S. C.; Fatima, A. de; Lepri, S. R.; Sartori, D.; Ribeiro, L. R. [UNESP]; Mantovani, M. S. (Sage Publications Ltd, 2014)
(R)-Goniothalamin (R-GNT) is a secondary metabolite isolated from the plants of the genus Goniothalamus. This molecule has attracted the attention of researchers because of its selective cytotoxicity against tumor cells and its ability to induce apoptosis. (S)-Goniothalamin (S-GNT) is a synthetic enantiomer of R-GNT, and its mechanism of action is largely unknown. In this study, we investigated the activity of S-GNT in a human non-small cell lung cancer NCI-H460 cells. We observed that the cells exposed to this compound exhibited cytotoxicity in a concentration-dependent manner. Based on the data obtained through the assessment of apoptosis induction in situ and the comet assay, we suggest that this cytotoxicity occurs due to the potential ability of this molecule to induce DNA damage with the consequent induction of cell death via apoptosis. A significant reduction in the messenger RNA levels of baculoviral inhibitor of apoptosis repeat-containing 5 (BIRC5) gene that encodes the survivin protein was found. This novel finding may explain the inhibition of cell proliferation and induction of apoptosis in tumor cells caused by this compound.
Keywords: Apoptosis; BIRC5; cytotoxicity; genotoxicity; (S)-goniothalamin; survivin